Low Flow Trends in Texas Stream Segments Serving Unique Hydrologic Functions - Kartik Venkataraman; Narayanan Kannan; Victoria Chraibi (Texas Water Journal, 2023)
In recognition of the unique hydrologic functions they serve, certain stream segments in Texas have been designated as ecologically significant. In this study, we evaluated low flow trends in seven hydrologically unique stream segments spanning three climatic divisions in Texas from 1970 to 2019. Despite increasing mean annual temperatures, there are no trends in low flows or other hydrologic variables in the East Fork of the San Jacinto River in the Upper Coast climatic division, likely due to local moisture surplus effects from the Gulf of Mexico. In the Edwards Plateau climatic division, annual low flows and annual baseflows are decreasing in the South Fork of the Guadalupe River, the Sabinal River and the Frio River. While increasing mean annual temperatures appear to have a role in the drying of all three of these stream segments, increasing annual potential evapotranspiration may be an additional driver in the Sabinal and Frio Rivers. Analysis of the Standardized Streamflow Index indicates that all seven stream segments experienced their worst streamflow droughts in the 2010s. As such, the watersheds draining to the gages on these stream segments have minimal anthropogenic impacts, suggesting the influence of climate on the observed stream drying.